Development of a life cycle cost estimating framework for oil refineries - Okafor, Okechukwu Peter (Cranfield University, 2011)
This study is concerned with the understanding of some vital features of various life cycle costing methodologies and tools. Integrating these features with the refinery technical processes would assist in the development of a life cycle costing framework for oil refineries. The aim of this research is to develop a comprehensive life cycle cost estimating framework for the evaluation of not only the total cost and system effectiveness of new refineries but also the revamping, and maintenance of the existing refineries. Several conceptual life cycle costing models relating to various life cycle stages were reviewed, and their attachment to specific life cycle activities assessed. Furthermore, the literature review and the industry survey identified that a vital requirement for the development of a life cycle costing framework is the establishment of a structured conceptual life cycle costing model and a cost breakdown structure that will depict major cost categories and cost elements in the LCC framework. Consequently, a standard conceptual life cycle costing model and its cost breakdown structure were developed and integrated into a proposed LCC framework for oil refineries. A combination of the literature review findings and industry survey were also used to ascertain the current life cycle costing practice. It was identified that there is a lack of a practical framework to compare two or more options of refinery schemes for system effectiveness. This led to the development of a novel life cycle cost estimating framework that could be used in the evaluation of the total cost and system effectiveness of a new refinery when there is no performance data. Finally, the framework’s applicability and effectiveness was demonstrated through its application on a case study. The validation of the proposed framework and the cost estimates development within the case study was successfully carried out by experts from the industry and academia. Consequent upon the research findings, key areas for future work were identified. The implementation of the findings of this research within the industry could provide the much needed long-term benefit that comes with the formalisation of life cycle costing practice.